Adaptive physical education learning: evaluation by teachers of deafstudents at special elementary schools - Susanto, Nugroho; Setyawan, Hendra; Fitriady, Gema; Anam, Khoiril; García Jiménez, José Vicente; Latino, Francesca; Tafuri, Francesco; Eken, Özgür; Taufik, Muhamad Syamsul; Bahtra, Ridho; Sazeli Rifki, Muhamad; Hafidz, Abdul; et al. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. This research aims to evaluate adaptive physical education learning in deaf students at special elementary schools.Methods. This study employs an evaluation model approach to assess the efficacy of adaptive physical education instruction.Specifically, this research utilizes the CIPP (Context, Input, Process, and Product) model for evaluation. The participantsin this study were teachers who taught physical education in West Sumatra, with a sample size of 60 teachers in West Sumatra,Indonesia. Data collection was carried out using a research instrument in the form of a questionnaire administered via GoogleForms. The results showed that all statement items of the questionnaire were valid for reliability testing.Results. The results of this research showed that the evaluation using the context and input components of the CIPP scored74.32% and 70.71%, respectively, indicating both as good. However, the process and product aspects attained a score of 50.83%and 48.10% indicating them as enough.Conclusions. This research concluded that the implementation of adaptive physical education learning for deaf studentswas good. Based on the results, this research recommends that evaluations be conducted at the school level for students withspecial needs. Additionally, evaluation is also needed using participants involved in education.
Keywords: adaptive; evaluation; physical education learning; deaf students; special elementary schools